PENGARUH PENERAPAN MODEL NHT TERHADAP HASIL BELAJAR SISWA KELAS X IPS SMAN 2 NGABANG - Andriana, Selvina; Margiati, K.Y.; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThis study aims to determine the effect of the application of NHT on the learning outcomes of class X IPS students of SMAN 2 Ngabang. The research method used was an experiment with the form of Quasi Experiment Design and the research design for Nonequevalent Control Group Design. The population is all of the X IPS classes totaling 131 people, the sample of this study is class X IPS 4, which amounts to 33 students as the experimental class and students of class X IPS 3, amounting to 32 students as the control class. Data collection techniques using measurement techniques and data collection tools are written tests of objective forms in the form of multiple choices. The results of the study showed that the final test of the control class was 69.81 and the final test average of the experimental class was 77.45. The results of the t-test were obtained tcount of 3.27 and t table (Î± = 5% with dk = 63) of 1.6703, which means thitung (3.27)> t table (1.6703), then Ha is accepted. So, it can be concluded that there is an effect of the application of NHT on the results of the learning outcomes of class X IPS students of SMAN 2 Ngabang. Calculation of Effect Size (ES), obtained ES for 0.87 (high category). Based on these calculations, it can be said that the application of NHT has a positive influence on the learning outcomes of class X IPS students of SMAN 2 Ngabang.Keywords: Influence, NHT, Learning Outcomes.